2016 ASEE Annual Conference &Amp; Exposition Proceedings
DOI: 10.18260/p.27305
|View full text |Cite
|
Sign up to set email alerts
|

Grading for Enhanced Motivation and Learning

Abstract: Lizabeth is a professor at Cal Poly, SLO in Industrial and Manufacturing Engineering. She has been teaching for 23 years and has continued to develop innovative pedagogy such as project based, flipped classroom and competency grading. Her current research examines grading and the assumptions faculty hold about students. Through the SUSTAIN SLO learning initiative she and her colleagues have been active researching transformation in higher education. Dr. Linda Vanasupa, California Polytechnic State University, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Students are driven by grades. The topic of student motivation has been studied extensively and students make many of their decisions through the lens of the grade-driven environment [12]. In our own teaching experience, we have found that there appears to be an addiction, of sorts, to scoring.…”
Section: Mastery-based Gradingmentioning
confidence: 80%
“…Students are driven by grades. The topic of student motivation has been studied extensively and students make many of their decisions through the lens of the grade-driven environment [12]. In our own teaching experience, we have found that there appears to be an addiction, of sorts, to scoring.…”
Section: Mastery-based Gradingmentioning
confidence: 80%
“… Assignments that require students to connect with a professional engineer or alumni for an interview could help expand a network for the students (Social Capital).  Changes in grading practices, such as forms of mastery grading, could help students use their resistant capital where they can master content through multiple tries at exams [9].…”
Section: Design Courses Based On Students' Strengthmentioning
confidence: 99%
“…Traditionally, higher education coursework has been delivered through lectures and grades have been assigned as a way of assessing achievement of coursework. There is abundant literature supporting what has been described as outcomes-based or competency-based education since the 1970's, [8][9][10][11][12][13][14][15][16][17][18][19] including research projects involving engineering courses. [20][21][22][23][24][25][26] Indeed, there has been a shift in education in recent decades from an emphasis on teaching to an emphasis on learning.…”
Section: Traditional Education and Assessmentmentioning
confidence: 99%